Washington State Recreational Marijuana Legalization: Parent and Adolescent Perceptions, Knowledge, and Discussions in a Sample of Low-Income Families - Mason, W. Alex (Subst Use Misuse, 2015)
BACKGROUND: In November 20012, Washington State and Colorado became the first states in the United States to legalize recreational marijuana use for adults, and Uruguay became the first country to allow the cultivation, distribution, possession, and use of marijuana. One possible consequence of these changes is increased adolescent marijuana use. Parents may mitigate this adverse consequence; however, whether parents and adolescents have accurate knowledge about the laws and are discussing marijuana use in light of the law changes is unknown. OBJECTIVE: We examine perceptions, knowledge, and parent-child discussions about Washington State’s recreational marijuana law in a sample of low-income families. METHODS: Participants were a subset of families (n = 115) in an ongoing study that originally recruited parents and adolescents from middle schools in Tacoma, Washington. In summer 2013, when students were entering the 11(th) grade, students and their parents were asked questions about the recreational marijuana law. RESULTS: Participants perceived that their marijuana-related attitudes and behaviors changed little as a result of the law, and displayed uncertainty about what is legal and illegal. Most parents reported discussing the new law with their children but only occasionally, and conversations emphasized household rules, particularly among parent lifetime marijuana users compared to non-users. CONCLUSIONS/IMPORTANCE: Results suggest that there should be a public health campaign focused on families that provides clear information about the recreational marijuana laws.